MENINGKATKAN KEMAMPUAN GURU SEKOLAH BINAAN MENYUSUN EVALUASI BELAJAR AKHIR SEMESTER GANJIL MELALUI PEMBERIAN TUGAS DIAKHIRI WORKSHOP PADA SD NEGERI 025 MENAMING - Tiana, Hj. (Universitas Pasir Pengaraian, 2017)
Prepare the final semester test results to measure the success of students in mastering basic competence indicators at the end of the semester, by looking at the results of teachers will know the weaknesses of students. To be able to compile a test that meets the requirements is quite difficult because preparing the test requires knowledge, skill and high accuracy. This research is descriptive qualitative research. This research was conducted in SD Negeri 25 Menaming with total teachers of 14 teachers. The purpose of this study is to describe the level of mastery of the ability of teachers in preparing the evaluation of learning (test) through the assignment of the workshop ended. The methods used in this study include test methods, observation methods, and interview methods. The application of the workshop in preparing the final semester test result is very effective. Attitude and ability of teachers of SD Negeri 25 Manaming after giving the assignment ended the workshop was satisfied, because through the assignment that ends the workshop can use the time so it is not delayed. Through the workshop can also improve the ability of teachers in preparing the test, it is seen in the first cycle activity average value 57 Tests are considered feasible if at least 75% of criteria can be met. Then the workshop cycle II, then a complete 10 people (78%), so that more skilled school teachers entirely make the problem in the future, then proceed to cycle III with workshops where teachers have made a matter of home for verification or study. So after being assessed in the workshop III cycle of this result is very satisfactory that complete 14 people with 100% percentage was able to arrange the final semester test results.